The impact of regional institutional quality on economic growth and resilience in the EU - Marinela-Daniela Filip; Ralph Setzer (European Central Bank (ECB), 2025)
This paper investigates the impact of regional institutional quality on economic growth and economic resilience. Using data collected by the Quality of Government Institute, we conduct a two-way fixed effect panel regression model for around 200 European regions during the period 2010 to 2021. Our findings establish a positive relationship between institutional quality and medium-term GDP growth. This effect is more pronounced in regions with low-income per capita, highlighting the importance of asymmetries across European regions. A convergence of regions with low institutional quality to the EU median would increase annual GDP per capita growth by 0.5 percentage points over the medium-term. Additionally, regions with high quality institutions are more resilient to adverse shocks and have a lower incidence of crisis. Our results suggest that regional institutional reforms, such as increasing public sector efficiency or reducing corruption, would spur growth, resilience, and convergence in the European economy.
Keywords: O43; E02; R11; R50; C23; 330; Regional Institutional Quality; Resilience; EU; Reforms; Economic Growth; regional economy; econometrics; institutional reform; public administration